2021
DOI: 10.1136/gutjnl-2021-324071
|View full text |Cite
|
Sign up to set email alerts
|

Suppressor CD4+T cells expressing HLA-G are expanded in the peripheral blood from patients with acute decompensation of cirrhosis

Abstract: ObjectiveIdentifying components of immuneparesis, a hallmark of chronic liver failure, is crucial for our understanding of complications in cirrhosis. Various suppressor CD4+ T cells have been established as potent inhibitors of systemic immune activation. Here, we establish the presence, regulation and mechanism of action of a suppressive CD4+ T cell subset expressing human leucocyte antigen G (HLA-G) in patients with acute decompensation of cirrhosis (AD).DesignFlow cytometry was used to determine the propor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 53 publications
(39 reference statements)
0
2
0
Order By: Relevance
“…For the first time, this study provided a relatively accurate tool to predict the risk of sepsis among patients with liver cirrhosis, which demonstrated good discrimination and calibration power. There were three noteworthy features in our study: (1) a large number of patients were included in the study; (2) the variables used in the model can easily be obtained in the clinical setting; and (3) the nomogram demonstrated greater predictive performance in both training and validation cohorts. Many experimental and clinical studies have demonstrated that sepsis and infectious diseases differ according to gender.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For the first time, this study provided a relatively accurate tool to predict the risk of sepsis among patients with liver cirrhosis, which demonstrated good discrimination and calibration power. There were three noteworthy features in our study: (1) a large number of patients were included in the study; (2) the variables used in the model can easily be obtained in the clinical setting; and (3) the nomogram demonstrated greater predictive performance in both training and validation cohorts. Many experimental and clinical studies have demonstrated that sepsis and infectious diseases differ according to gender.…”
Section: Discussionmentioning
confidence: 99%
“…Liver cirrhosis is a leading cause of death and morbidity worldwide in a wide range of chronic liver diseases, 1 characterized by diffuse fibrosis, disruption of intrahepatic venous flow, and portal hypertension, which may result in liver failure. 2 There are nearly two million deaths caused by liver cirrhosis each year, making liver cirrhosis one of the top 10 leading causes of death in the world. 3 , 4 Liver cirrhosis accounts for ~2% to 4% of all deaths worldwide.…”
Section: Introductionmentioning
confidence: 99%